63 Surgical staging for high-grade uterine serous carcinoma: is lymphadenectomy required?. (18th September 2019) - Casarin, J; Bogani, G; Piovano, E; Falcone, F; Ferrari, F; Odicino, F; Puppo, A; Malzoni, M; Greggi, S; Raspagliesi, F; Ghezzi, F
Abstract : Objectives: To assess the role of a systematic lymphadenectomy for surgical staging of high-grade uterine serous carcinoma (USC). Methods: Data of consecutive patients with apparent early stage USC surgically treated at six Italian tertiary referral cancer centers were analyzed. Data was compared between patients who had retroperitoneal staging including at least pelvic lymphadenectomy "LND" (±para-aortic) vs. patients who underwent hysterectomy alone "NO-LND". Baseline, surgical and oncological outcomes were analyzed. Survival curves were estimated, and the significant predictive prognostic variables were assessed. Results: 140 patients were analyzed, 106 LND and 34 NO-LND. NO-LND group (compared to LND) included older patients (median age 73 vs. 67 years), and with higher comorbidities (median CCI 6 vs. 5) (all p-values <0, 001). Surgical related outcomes and complications did not significantly differ between the groups. Similar recurrence rates were registered (LND 33, 1% vs. NO-LND 41, 4%; p=0, 240) and no significant difference in Disease-Free survival (DFS) was estimated (Log-Rank test, p=0, 084) among the groups, while overall survival (OS) was significantly poorer in NO-LND group (p<0, 001). Multivariable Cox proportional hazards regression analysis showed the presence of extra-uterine disease as independent predictor of DFS (HR 1, 530 – 7, 828, p= 0, 003). Regarding OS, both age (1, 044 -1, 150) and extra-uterine disease (1, 406 – 4, 701) were found as independent predictors. Conclusions: This large retrospective series showed no association between the systematic performance of lymphadenectomy and survival in patients undergoing surgical staging for apparent early-stage USC.